Implementation of two-way free space quantum key distribution - Abdul Khir , Mohd Fared; Mohd Zain, Mohd Norzaliman; ., Suryadi; Saharudin, Suhairi; Shaari, Sahbudin (SPIE, 2012)
We report an implementation of a two-way, four-state quantum key distribution (QKD) protocol (namely, the LM05 protocol) over a free space medium. A stable quantum bit error rate of 3.34% and maximum tolerable channel loss for secure key generation of 5.68 dB in the absence of a photon number splitting attack were recorded. The result strongly indicates the feasibility of a two-way QKD protocol implementation over a free space medium.